Learner Autonomy through Distance Learning Process, the Mediation of Technology - Lalidji, Mohamed Amine (LANGUAGE ART, 2023)
In the aim of this contribution is stressing the importance of distance learning in its relation to learner autonomy. Since the shift in the teaching paradigm from teacher-centeredness to student-centeredness, many solutions have been offered to make learning more autonomous and inspiring. The concept of autonomy presented by several authors regards proactivity of learners to access, browse, search content, and meet the demands of the teachers. This led the researchers to the conclusion that autonomy should first of all comes from within, thus, making the students responsible for their own learning. In the same time, we investigate how universities use the potential for emerging technologies under the banner of web 2.0 to facilitate the fulfillment of all learners’s needs and to enhance student online and distance learning. Through the use of the analytical approach, we reached these important results: 1-the role of technology mediation and online collaborative tools in supporting the distance learning, 2-the importance of achieving learner autonomy as a condition for the success of distance learning, 3- that technology and learner autonomy constitute the technical and cognitive requirements for the success of distance learning.